A compatible and crosslinked poly(2‐allyl‐6‐methylphenol‐co‐2, 6‐dimethylphenol)/polystyrene blend for insulating adhesive film at high frequency. Issue 31 (10th April 2019) - Lin, Yan‐Cheng; Chiang, Chi‐Haw; Kuo, Chih‐Cheng; Hsu, Sheng‐Ning; Higashihara, Tomoya; Ueda, Mitsuru; Chen, Wen‐Chang
ABSTRACT: A polymer blend consisting of poly(2‐allyl‐6‐methylphenol‐ co ‐2, 6‐dimethylphenol) (APPE) and polystyrene (PS) with additives such as 1, 2‐bis(4‐vinylphenyl)ethane, cyanate ester, and nitrile butadiene rubber was formulated as an insulating high‐frequency adhesive film. The polymer blend of APPE and PS showed very high compatibility to these additives, and the resulting thermally cured polymer blend exhibited an excellent mechanical strength, as shown by an ultimate tensile strength of 51 MPa and Young's modulus of 1.4 GPa. Moreover, the blend exhibited very good dielectric properties, with a dielectric constant of 2.3 and a dissipation factor of 0.0030 at 10 GHz. The glass‐transition temperature of the cured polymer blend was 141 °C, as determined by differential scanning calorimetry, and the 5% weight loss temperature was 372 °C, indicating relatively high thermal resistance characteristics. Furthermore, its peel strength to a copper foil reached 0.80 N/mm. The present study suggested that the thermally cured APPE/PS polymer blend with additives will have potential applications for the next‐generation high‐frequency adhesives in microelectronic circuits. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47828. Abstract : A polymer blend consisting of poly (2‐allyl‐6‐methylphenol‐ co ‐2, 6‐dimethylphenol) and polystyrene with additives such as 1, 2‐bis(4‐vinylphenyl)ethane, cyanate ester, and nitrile butadiene rubber was formulated as a high‐frequency adhesive. The polymer blends show excellent mechanical performance and low D k and low D f .